STUDI POTENSI EKOWISATA DANAU PULAU SATONDA DI DESA NAGAMIRO KECAMATAN PEKAT KABUPATEN DOMPU PROVINSI NUSA TENGGARA BARAT - Rugayah, Rugayah; Prakosa, Galit Gatut; Waskitho, Nugroho Tri; Cahyo, Febri Arif (Journal of Forest Science Avicennia, 2018)
Satonda Island Lake is a tourist attraction that attracts many tourists, both local and foreign tourists, and has abundant biodiversity in the form of flora and fauna. However, the management of the area has not been carried out optimally, both in terms of facilities and infrastructure and the involvement of the local government and community in its management. The purpose of this study was to find out the strategy for developing ecotourism on Satonda Island Lake. Data through field observations, documentation, questionnaires, and interviews to obtain data related to the potential of ODTWA (Nature Tourism Attraction Objects), tourist facilities and infrastructure, as well as public perceptions and interests of visitors. Data were analyzed through SWOT analysis to determine the strategy for developing ecotourism on Satonda Island Lake. The results of the SWOT analysis show that the development of Satonda Island Lake ecotourism is prioritized using SO (strength and opportunities) strategies with the consideration that ecotourism resources have considerable potential, but have not been utilized optimally.